MULTIVARIATE ANALYSIS OF GENETIC DIVERGENCE AMONG NIGER GENOTYPES IN RELATION TO SEED OIL QUALITY TRAITS - S. C. PULATE; H. S. PATIL; M. R. PATIL (The Bioscan, 2013)
A study was conducted to assess the extent and pattern of genetic variability of niger genotypes with respect to twelve seed oil quality traits in forty niger genotypes. The analysis of variances has shown that there was significant variation among the genotypes in all traits. The high heritability (>60%) was recorded for all oil parameters except for gamma tocopherol (2.80%). The multivariate analysis has resulted in formation of eleven clusters. Out of eleven clusters formed, cluster 1 was the largest with eighteen genotypes followed by cluster 4 with six genotypes. The highest genetic distance was recorded between cluster 7 and 11 (28.19), while lowest genetic distances noticed between cluster 6 and 7 (8.24). Cluster 2 included four genotypes with highest means for oil content (39.83), protein (33.51), oleic acid (36.53), stearic acid (10.31), alpha tocopherol (94.42) and gamma tocopherol (7.50). Thus, on the basis of present finding there is a possibility of simultaneously improving the fatty acid profile, tocopherol as well as the oil content with seed yield per plant of the genotypes through inter crossing between genotypes viz., JNS-164, JNS-165, Utakal Niger -150, GA-10, IGPN-08-66, IGPN-2004-1, JNS-501, IGPN-8004 and BAU-10-5. Among twelve traits studied palmatic acid (28.97%) contributed highest towards the genetic divergence followed by linoleic acid (27.44%) and stearic acid (18.46%).